The Limited Liability Company: Lessons for Corporate Law - Jonathan R. Macey (Washington University Law Quarterly, 1995)
This Article explores the implications of the emergence of the limited liability company for our understanding of corporate law. What does the modem emergence of the limited liability company tell us about the state of American corporate law? This Article argues that the emergence of the limited liability company has much to tell us about a variety of important topics in corporate law, particularly the reasons for requiring formal incorporation, jurisdictional competition for corporate charters, the costs and benefits of limited liability, and the structural problems that may hamper sweeping reform of corporate and tort law rules affecting enterprise and investor liability.
Keywords: Private companies